Industrial safety management and its impact on occupational risk in a Peruvian company - Flores Lezama, Marilú Trinidad; Abanto Alvarez, Sarai Indira; Calderón Goicochea, Ana Adalid; Rojas Abanto, Jenifer Lizeth; Aguilar Chávez, Pablo Valentino (LACCEI, 2023)
The present investigation entitled "Management of industrial safety and its incidence in the occupational risk of the Molino Espiga del Norte E.I.R.L., Guadalupe, 2023". Its general objective was to determine the incidence of industrial safety management in occupational risk. The methodology that was required was of the applied type of quantitative approach, with a non-experimental - cross-sectional design. The population and sample was made up of 30 workers who work at the Molino Espiga del Norte E.I.R.L. District of Guadalupe, to which the Likert-type scale questionnaire was used as an instrument to collect the information that it contributes with the investigation. Likewise, the data obtained were organized and processed in the statistical programs SPSS V25 and Excel 2019. The results found indicate that there is a high positive relationship of (r=0.652; p= 0.000) between industrial safety management and occupational risk. In the same way, it was possible to observe that there is a high positive Spearman correlation of (r= 0.640) between teamwork and occupational risk. On the other hand, it was found that there is no correlation between job satisfaction and occupational risk, the significance value of (p=0.646) being greater than 5%. Likewise, it was possible to appreciate that there is a correlation between supervision and occupational risk, with the significance value of (p= 0.000) being less than 5%. It is concluded that, as long as good industrial safety management is carried out, occupational risk management will be optimized.